Baseline hemoglobin as a prognostic factor for radiotherapy outcomes and survival in advanced cervical cancer at Dr. Kariadi General Hospital, Semarang, Indonesia - Mona Galatia Marpaung; Teukur Mirza Iskandar; Noor Pramono; Suhartono (Universitas Airlangga, 2026)
HIGHLIGHTS Baseline hemoglobin level is a relevant predictive factor in cervical cancer management, emphasizing the importance of maintaining optimal hematological status to enhance therapeutic effectiveness and improve patient survival. Patients with hemoglobin levels =11 g/dL demonstrated higher two-year survival rates and longer median survival times compared with those with levels <11 g/dL, supporting the role of hemoglobin as an important prognostic indicator of long-term clinical outcomes. ABSTRACT Objective: This study aimed to evaluate the relationship between baseline hemoglobin concentration and the effectiveness of radiotherapy in patients with advanced cervical cancer, with emphasis on survival outcomes and therapeutic response. Materials and Methods: A retrospective observational study was conducted using medical records from the Oncology Clinic and Radiotherapy Unit of Dr. Kariadi General Hospital, Semarang, Indonesia, between January 2017 and December 2022. Eligible subjects included women diagnosed with stage IIB–IIIB cervical cancer who had completed radiotherapy, either alone or combined with chemotherapy. Hemoglobin levels were compared between treatment groups using the chi-square test. Survival probabilities were assessed using Kaplan–Meier analysis and compared with the log-rank test, with p <0.05 considered statistically significant. Results: A total of 939 patients met the inclusion criteria. Among them, 89 patients received box system radiotherapy and 850 underwent brachytherapy. Hemoglobin levels <11 g/dL were observed in 55.1% of patients in the box system group and 42.7% in the brachytherapy group. Conversely, hemoglobin levels ≥11 g/dL were more frequent in the brachytherapy group (57.3%) than in the box system group (44.9%) (p = 0.034). Patients with hemoglobin levels ≥11 g/dL had a higher two-year survival rate (67.4%) compared with those with hemoglobin levels <11 g/dL (54.9%). Mean survival time was also longer in patients with higher hemoglobin levels (19.8 vs 17.4 months). Conclusion: Baseline hemoglobin level is significantly associated with radiotherapy outcomes and survival in advanced cervical cancer. Higher hemoglobin levels (≥11 g/dL) are associated with improved survival and reduced mortality, highlighting its role as an important prognostic indicator. Maintaining adequate hemoglobin levels may improve treatment effectiveness and clinical outcomes.